Time in Polish Prehistoric Archaeology in the Nineteenth and Early Twentieth Century - Ryszewska, Katarzyna (Instytut Historii im. Tadeusza Manteuffla Polskiej Akademii Nauk, 2024)
The nineteenth century marked the emergence of Polish archaeology in terms of defining time and the continuity of past events reconstructed based on material sources. The article offers an account of the changing perception of time in Polish prehistoric archaeology during the nineteenth and early twentieth century while assessing the impact of specific contemporary discoveries and archaeological studies on attempts at chronology and periodisation of prehistoric time. These discoveries broadened the knowledge of the continuity of events that took place within particular prehistoric ages and periods. As a result, the previously accepted “short” chronology of prehistoric times had been lengthened, and an evolutionary model replaced the biblical image of human time.
p. 93-111
Keywords: nineteenth century; history of Polish archaeology; prehistory; time; relative chronology; absolute chronology; archaeology - Poland - history; stone age - chronology; time perception - history